Analisis Kebijakan Pemberantasan Narkotika Di Indonesia Dalam Perspektif Kriminologi - Laksa Bayu Bahaduri; Vinita Susanti (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
Illicit Trafficking and Abuse of Narcotics and illegal drugs at this time can be said to be anextraordinary crime and get a strong spotlight in various circles, both in society, government and eveninternationally. This is because the negative impact that can be caused by the abuse of Narcotics is verylarge and detrimental in terms of health, economy, social, culture and even aspects of national security.Policies are directly or indirectly influenced from international and national aspects in the prevention anderadication of drugs, there are still some weaknesses in government policies in the overall criminal justicesystem, especially the correctional system in the field of eradication in dealing with narcotics abuse andillicit trafficking. This research is a type of literature study research by looking for data and informationreferences and theories that are relevant to the cases or problems found. The conclusion of this study is amodel of a centralized penitentiary specifically for narcotics convicts supported by the participation ofrelevant stakeholders in its implementation and supervision